How Acceptable Are Their Obstacles to Reentry? Attitudes of Community Corrections Professionals Toward Collateral Consequences for Sex Offenders. Issue 4 (2nd October 2017) - Call, Corey
ABSTRACT: Numerous collateral consequences have been attributed to current sex-offender management policies. The present study analyzed the perceptions held by community corrections professionals toward the acceptability of various collateral consequences experienced by sex offenders in the community. Potential influencing factors including demographic variables, belief in the cause of sex offending, and punishment philosophy were considered. Results indicate overall low levels of acceptability for collateral consequences as by-products of current sex-offender management policies; however, noticeable portions of community corrections professionals were either unsure of their feelings or felt certain collateral consequences are acceptable. Furthermore, to varying degrees, punishment philosophy, belief in the cause of sex offending, age, parental status, and race were significant predictors of perceived acceptability.